The efforts of women victims of domestic violence in maintaining marriages - Anisatul Badiah (Jurnal Sosiologi Dialektika, 2022)
Most of the incidents of domestic violence happen to women as victims, but even though they have accepted acts of violence, women still maintain their marriages. From the existing phenomena, this study reveals the motives of female survivors of former domestic violence victims in maintaining their marriage. This study used qualitative research method. The research subjects were female survivors of former domestic violence victims assisted by WCC Jombang, who were selected based on certain criteria. The results of the study show that the behavior of maintaining the integrity of the marriage is based on the â€œin order to motiveâ€ and the â€œbecause motiveâ€. Because the motive for maintaining a marriage is a consideration of the close relationship between a son-in-law and a mother-in-law, a son-in-law and a brother, hindered by the husbandâ€™s profession, and the consideration of children. In the â€œin-order-toâ€ motive action to maintain the marriage, the hope is that the family will return to being intact, there will be no violence, no third person, and return to harmony. Furthermore, in order to maintain the marriage, the wife carried out mediation efforts, rearranged the household, asked for protection from the authorities, and assisted the Jombang WCC. This study can be concluded that the existence of in order to motive and action because motive in the wife makes the wife able to maintain the marriage and able to form new knowledge.